STRATEGI MEMPERTAHANKAN USAHA PEDAGANG KAKI LIMA (PKL) DI MASA PANDEMI COVID19 - Hanna Zulhijahyanti; Kintan Ayu Agnes Safira; Leonita Lisha Saputri; Erwin Permana (Universitas Pamulang, 2021)
One of the informal sector Micro and Small Business actors who feel the significant impact of the Covid-19 pandemic is street vendors (PKL). This study aims to explain the business strategy of street vendors in order to be able to maintain their survival in the businesses that will be carried out (PKL) during the Covid-19 pandemic. This research is included in qualitative research. From the results of the research, the marketing strategy used by street vendors in the midst of the Covid-19 pandemic is by using social media, including Facebook, Instagram, Whatsapp, telegram, and joining other online businesses such as shopee, go-food, and grap- food. By using social media, buyers and traders can easily make transactions without having to touch. it can be explained that the survival strategy can work as expected by paying attention to the purchasing power of consumers during the Covid-19 pandemic.